Fauna flebotomínica em área endêmica de leishmaniose visceral em Aracaju, Estado de Sergipe, Nordeste do Brasil - de Jeraldo, Verónica Lourdes Sierpe; de Góes, Marco Aurélio Oliveira; Casanova, Claudio; de Melo, Claudia Moura; de Araújo, Edilson Divino; Filho, Sinval Pinto Brandão; Cruz, Danilo Esdras Rocha; Pinto, Mara Cristina [UNESP] (FapUNIFESP (SciELO), 2012)
Introduction: In recent years, visceral leishmaniasis, a major public health problem, has been spreading from the rural to urban areas in many areas of Brazil, including Aracaju, the capital of the State of Sergipe. However, there are no studies of the sandfly fauna in this municipality or its variation over the year. Methods: Phlebotomine sandflies were collected from a rural area of Aracaju from September 2007 to July 2009. Modified CDC ultra-violet (UV) light traps were used to evaluate sandfly monthly distribution and their presence in the domestic and peridomestic environments. Results: The most abundant species was Lutzomyia longipalpis (90.4%) followed by Evandromyia lenti (9.6%). A chicken shed trap site had the highest proportion of L. longipalpis (51.1%) and large numbers of L. longipalpis were also collected in the houses closest to the chicken shed. There was a positive correlation between monthly rainfall and L. longipalpis abundance. Conclusions: Lutzomyia longipalpis is the most abundant species and is probably the main vector of the visceral leishmaniasis agent in the rural area of Aracaju. An increase in L. longipalpis frequency was observed during the rainy season. The peridomicile-intradomicile observations corroborate the importance of chicken sheds for the presence of L. longipalpis in the peridomestic environment. The great numbers of L. longipalpis inside the houses confirm the endophilic behaviour of this species and the possibility of visceral transmission in the intradomicile.
Sandfly fauna in an area endemic for visceral leishmaniasis in Aracaju, State of Sergipe, Northeast Brazil
Keywords: Lutzomyia; Phlebotominae; Sandfly; Sergipe